Requirements for the Design of the Household Part in Modern Production Buildings (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article describes the rules for designing sanitary facilities in modern industrial buildings, design requirements, and issues of creating comfort for employees in the building.